Molecular cloning of two C/EBP-related proteins that bind to the promoter and the enhancer of the alpha 1-fetoprotein gene. Further analysis of C/EBP beta and C/EBP gamma. - Thomassin, H (1992)
In an attempt to identify proteins that may regulate alpha 1-fetoprotein (AFP) gene expression, we screened a cDNA expression library from neonatal rat liver with two essential cis-elements of the AFP promoter and enhancer. We isolated two cDNAs which were found to correspond to leucine zipper proteins of the CC-AAT/enhancer binding protein (C/EBP) family: C/EBP beta and C/EBP gamma. The three related proteins C/EBP alpha, beta and gamma bind with indistinguishable specificity to multiple DNA sites in the promoter and the enhancer of the AFP gene. In addition, C/EBP beta and C/EBP gamma readily heterodimerize with each other as well as with C/EBP alpha. The mRNAs coding for C/EBP beta and C/EBP gamma are expressed in a wider variety of rat tissues than C/EBP alpha mRNA, including yolk sac and fetal liver. The steady-state levels of C/EBP alpha, beta and gamma mRNAs increase during liver development, in parallel with their respective gene transcriptional rates. The high levels of C/EBP beta and gamma mRNAs in rat yolk sac and fetal liver, where C/EBP alpha is poorly expressed, suggest that C/EBP beta and/or gamma could be preponderant or early regulators of the AFP gene in these tissues.